GRAMMAR AND STYLE OF LEGAL TEXTS (CODE CASE STUDY) - KORNIECKA, Diana (Comparative Legilinguistics, 2010)
The purpose of the paper is to present obstacles in the translation process of Russian and Polish penal codes. Both texts are characterized by a particular register and structure that are regulated by separate laws in both countries. The paper also gives an account of selected differences in macro and micro text structures of the given material. The result to emerge from comparative analysis is that ignoring formal guidelines in the translation process of codification acts may lead to style distortion, that is to say to a translation mistake. On the question of structure and semantics of legal instruments, this study shows that a knowledge of legislative technique is of significant importance for a translator.